PUERICULTURE INTEGRATING SERVICE AND LEARNING: A COLLECTIVE CONSTRUCTION - Chayenne Guttierrez Haragushiku; Letícia Bertoldi; Silvia Cristina Mattos; Verônica de Azevedo Mazza (Universidade Federal do Paraná, 2001)
This paper presents the sub-project of the program of institutional joint in the health area: Nursing department and the municipal health division of Colombo, it has the go of contributing in the reduction of the children death rate of the city. Aerts (1997), says that the reduction on the children death rate is connected with improvements in health attendance, expansion of the basics health services network, programs turned to high risk social groups, incentive to breast feeding and vaccines campaigns. This expansion program gave birth to the puericulture program done at the Alto Maracanã Health Unit in the city of Colombo in 1998, being developed by the extension scholarship studentes of UFPR (Federal University of Paraná) and of the Municipal Health division. It´s pre set activities are: Nurse attending, analysis of the risk factors and spreading the project to all of the city's health unites. These actions between the learning institution and public services attempt to provide the planning of health attending, showing the necessity of taking the child health issues as priorities improving the life quality of the child, your family and community.